2020
DOI: 10.1128/aem.03004-19
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Prevents Fatty Liver Disease, Decreases Serum Triglycerides, and Maintains Gut Homeostasis

Abstract: The objective of this study was to elucidate the effect of intestinal Akkermansia muciniphila bacteria on fatty liver disease. Five-week-old C57BL/6N mice were administered either phosphate-buffered saline (PBS; control) or A. muciniphila at 108 to 109 CFU/ml, and were fed either a 45% fat diet (high-fat diet [HFD]) or a 10% fat diet (normal diet [ND]) for 10 weeks. After 10 weeks, the mice were euthanized, and blood and tissue samples, including adipose tissue, cecum, liver, and brain, were immediately collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 36 publications
3
100
0
3
Order By: Relevance
“…Its depletion has been implicated in obesity and fatty liver disease, and supplementation of Akkermansia has even been shown to decrease serum triglyceride and alanine aminotransferase levels in obese mice. 27 Recently, Addolorato et al published their findings of significant Akkermansia reduction in patients with alcohol use disorder, irrespective of the degree of liver disease. 28 In line, Grander et al found a depletion of Akkermansia in fecal samples from alcoholic hepatitis patients and Akkermansia supplementation protected mice against liver injury in experimental alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Its depletion has been implicated in obesity and fatty liver disease, and supplementation of Akkermansia has even been shown to decrease serum triglyceride and alanine aminotransferase levels in obese mice. 27 Recently, Addolorato et al published their findings of significant Akkermansia reduction in patients with alcohol use disorder, irrespective of the degree of liver disease. 28 In line, Grander et al found a depletion of Akkermansia in fecal samples from alcoholic hepatitis patients and Akkermansia supplementation protected mice against liver injury in experimental alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitation of 16S rRNA pyrosequencing, we cannot identify the specific species that may produce IPA. However, Clostridium sporogenes is the only proved intestinal bacteria to produce IPA ( 32 ). Given the elevated growth of Clostridium XIVa induced by DNJ and its positive correlation with IPA content, we conclude that DNJ female specifically alters the composition of the gut microbiota, characterized by the enrichment of certain members in Clostridium XIVa, to stimulate IPA generation, ultimately ameliorating hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…A. muciniphila, considered a promising probiotic, is known to have important value in improving host metabolic functions and immune responses (Derrien et al, 2017;Plovier et al, 2017;Zhang et al, 2019). Recent studies support a protective effect of A. muciniphila against hepatic injury, steatosis, and neutrophil infiltration (Wu et al, 2017;Kim et al, 2020). A. muciniphila also protects against ethanol-induced gut leakiness, enhanced mucus thickness, and tight-junction expression (Grander et al, 2018).…”
Section: Discussionmentioning
confidence: 99%